Griscelli Syndrome with hemophagocytosis: a case report - Chavan, Vinod P.; Channakeshvala, Srikanth; Bhandary, Neeviya J.; Jayakumar, Haridharshan G.; Joshi, Suhas N. (International Journal of Contemporary Pediatrics, 2016)
Griscelli syndrome is a rare autosomal recessive disorder characterized by pigmentary dilution of the skin and the hair (silver hair), the presence of large clumps of pigment in hair shafts, and an accumulation of melanosomes in melanocytes. In one variant, hepatosplenomegaly, lymphohistiocytosis, and a combined T-cell and B-cell immunodeficiency are pronounced. The associated immunodeficiency often involves impaired natural killer cell activity, absent delayed-type hypersensitivity, and a poor cell proliferation response to antigenic challenge. Occasionally, impaired lymphocyte function and an inability to produce normal levels of immunoglobulins have also been described. In another variant, neurologic signs are most prominent. We present a case of 1 year male who presented with fever, jaundice, silver hair, heptoslenomegaly, and pancytopenia.